Learners’ perceptions of using English songs as a media for out of class listening activities - Zakly, Bayu Rafiq; Sukmawati, Farah Wahidah; Herlina (Research and Innovation in Language Learning, 2025)
The statement of the problem is formulated as follows: "How do learners’ perceptions of using English songs as a media outside of the classroom impact their listening comprehension." This research was conducted in qualitative research. Qualitative research is a type of research that aims to explore information deeply and openly on various responses. This research tries to get people to express their thoughts on a topic without giving them much guidance or direction. In this study, the researcher distributed interview questions to the subjects, then recorded each subject’s answers using a voice recorder. The results of the questionnaires and interviews show that English songs help students to learn and improve their listening comprehension.